2020
DOI: 10.3390/ijerph17030943
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cadmium Exposure and Taste and Smell Dysfunction: Results from the National Health and Nutrition Examination Survey (NHANES), 2011–2014

Abstract: Background: Cadmium is a ubiquitous environmental pollutant and has been associated with many adverse health outcomes. However, little is known about the effect of cadmium exposure on taste and smell dysfunction. Methods: We used the National Health and Nutrition Examination Survey (NHANES) 2011–2014 to investigate the associations between blood cadmium and taste and smell dysfunction among 5038 adults aged 40–80 years old. Taste and smell dysfunction were defined by questionnaires, examinations, or both crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
(37 reference statements)
0
6
1
Order By: Relevance
“…Blood cadmium levels in the BOSS were slightly lower than those reported in National Health and Nutrition Examination Surveys (NHANES), 1999-2010 . A recent study in NHANES, 2011-2014 found no association between blood cadmium level and measured olfactory dysfunction, but the NHANES study was cross-sectional compared with the long-term prospective design of our study …”
Section: Discussioncontrasting
confidence: 76%
“…Blood cadmium levels in the BOSS were slightly lower than those reported in National Health and Nutrition Examination Surveys (NHANES), 1999-2010 . A recent study in NHANES, 2011-2014 found no association between blood cadmium level and measured olfactory dysfunction, but the NHANES study was cross-sectional compared with the long-term prospective design of our study …”
Section: Discussioncontrasting
confidence: 76%
“…The adverse human health effects of Cd metal, on the other hand, should not be underestimated. For instance, Cd exposure has been shown to bring about both taste and smell dysfunctions in China [ 69 ]. Excessive Cd level in the body can cause hepatotoxicity, osteoporosis, teratogenicity, neurotoxicity and immunosuppression due to apoptosis induction in normal human mononuclear cells [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that environmental pollutants, including particulate matters, heavy metals, pesticides, and other organic pollutants, elicit neurodegeneration and olfactory dysfunction in human beings and animals, particularly in rat and fish. , For instance, Cd exposure was found to have no effect on the 1-octanol detection sensitivity in mice but led to dysfunction in olfactory learning and memory . Cd exposure at sublethal concentrations induced cell death and structural alterations in olfactory epithelium and caused behavioral deficits in zebrafish, Danio rerio .…”
Section: Introductionmentioning
confidence: 99%